2014
DOI: 10.1038/ncomms5486
|View full text |Cite
|
Sign up to set email alerts
|

Microglial displacement of inhibitory synapses provides neuroprotection in the adult brain

Abstract: Microglia actively survey the brain microenvironment and play essential roles in sculpting synaptic connections during brain development. While microglial functions in the adult brain are less clear, activated microglia can closely appose neuronal cell bodies and displace axosomatic presynaptic terminals. Microglia-mediated stripping of presynaptic terminals is considered neuroprotective, but the cellular and molecular mechanisms are poorly defined. Using 3D electron microscopy, we demonstrate that activated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
245
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(262 citation statements)
references
References 48 publications
15
245
1
1
Order By: Relevance
“…*Po0.05, **Po0.01, ***Po0.001 modulating neuronal growth, remodeling and survival. 21,49,50 In light of our previous findings, 11 sPIF downregulates microRNA let-7 expression through PI3K/Akt signaling, also in a TLR4-dependent manner reducing neuronal death. Meanwhile, decreased let-7 levels lead to increased expression of IL10, a direct target of let-7-mediated inhibition 55,56 and a potent anti-inflammatory cytokine in neuroprotection.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…*Po0.05, **Po0.01, ***Po0.001 modulating neuronal growth, remodeling and survival. 21,49,50 In light of our previous findings, 11 sPIF downregulates microRNA let-7 expression through PI3K/Akt signaling, also in a TLR4-dependent manner reducing neuronal death. Meanwhile, decreased let-7 levels lead to increased expression of IL10, a direct target of let-7-mediated inhibition 55,56 and a potent anti-inflammatory cytokine in neuroprotection.…”
Section: Discussionmentioning
confidence: 61%
“…20 In the case of brain injury, activation of the PKA/ PKC signaling pathways imparts neuroprotection by increasing expression of anti-apoptotic and neurotrophic molecules while reducing pro-apoptotic molecules in neurons. [21][22][23] Not surprisingly, PKA/PKC pathways have been recognized as potent targets for neuroprotective strategies.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Along with rod-shapedIba1 + cells, phagocytic (CD68 + ) and amoeboid Iba1 + cells increased in the cortex at later time points. The increase of Iba1 + cells seen within the cortex could be associated with the recently reported neuroprotective synaptic stripping; further analysis of the functional consequences of the observed neuroinflammation is needed [13] [37]. Perez-Polo et al [15] showed that at 6 hours after mild TBI one of the structures most affected by the pro-inflammatory cytokine IL-1β was the ipsilateral hippocampus.…”
Section: Discussionmentioning
confidence: 97%